A potential role for interleukin-15 in the regulation of human natural killer cell survival. - Carson, W E (1997)
Resting lymphocyte survival is dependent upon the expression of Bcl-2, yet the factors responsible for maintaining lymphocyte Bcl-2 protein expression in vivo are largely unknown. Natural killer (NK) cells are bone marrow-derived lymphocytes that constitutively express the beta and common gamma(c) subunits of the IL-2 receptor (R) as a heterodimer with intermediate affinity for IL-2. IL-15 also binds to IL-2Rbeta gamma(c) and is much more abundant in normal tissues than IL-2. Mice that lack the IL-2 gene have NK cells, whereas mice and humans that lack IL-2R gamma(c) do not have NK cells. Further, treatment of mice with an antibody directed against IL-2Rbeta results in a loss of the NK cell compartment. These data suggest that a cytokine other than IL-2, which binds to IL-2Rbeta gamma(c), is important for NK cell development and survival in vivo. In the current report, we show that the recently described IL-15R(alpha) subunit cooperates with IL-2Rbeta gamma(c) to transduce an intracellular signal at picomolar concentrations of IL-15. We demonstrate that resting human NK cells express IL-15R(alpha) mRNA and further, that picomolar amounts of IL-15 can sustain NK cell survival for up to 8 d in the absence of serum. NK cell survival was not sustained by other monocyte-derived factors (i.e., TNF-alpha, IL-1beta, IL-10, IL-12) nor by cytokines known to use gamma(c) for signaling (i.e., IL-4, IL-7, IL-9, IL- 13). One mechanism by which IL-15 promotes NK cell survival may involve the maintenance of Bcl-2 protein expression. Considering these functional properties of IL-15 and the fact that it is produced by bone marrow stromal cells and activated monocytes, we propose that IL-15 may function as an NK cell survival factor in vivo.